Cover Feature: Columnar Propeller‐Like 1, 3, 5‐Triphenylbenzenes: Probing the Effect of Chlorine on the Suzuki Cross‐Coupling and Liquid Crystalline Properties (Eur. J. Org. Chem. 15/2020). Issue 15 (14th April 2020) - Grunwald, Marco André; Wöhrle, Tobias; Forschner, Robert; Baro, Angelika; Laschat, Sabine
Abstract : The Cover Feature shows a star‐shaped triphenylbenzene which can be accessed through two different Suzuki–Miyaura couplings starting either from 1, 3, 5‐trisbromobenzene and the aryl‐MIDA‐boronate or from tris(pinacolboranyl)benzene and aryl bromide. Liquid crystalline properties, visualized by POM textures and SAXS diffraction patterns, were strongly dependent on the symmetry of the chloro vs. alkoxy substitution pattern. The cover was designed by Marco Grunwald. More information can be found in the Full Paper by S. Laschat et al.